FAIR environmental and health registry (FAIREHR) - Zare Jeddi, Maryam (2023)
Funding Information: Most co-authors were financialy supported with their respective inistitution. Some of the co-authors were financialy supportrd by the “Safe and Efficient Chemistry by Design (SafeChem)” project (grant no. DIA 2018/11) funded by the Swedish Foundation for Strategic Environmental Research, and by the PARC project (grant no. 101057014) funded under the European Union’s Horizon Europe Research and Innovation program. Publisher Copyright: Copyright © 2023 Zare Jeddi, Galea, Viegas, Fantke, Louro, Theunis, Govarts, Denys, Fillol, Rambaud, Kolossa-Gehring, Santonen, van der Voet, Ghosh, Costa, Teixeira, Verhagen, Duca, Van Nieuwenhuyse, Jones, Sams, Sepai, Tranfo, Bakker, Palmen, van Klaveren, Scheepers, Paini, Canova, von Goetz, Katsonouri, Karakitsios, Sarigiannis, Bessems, Machera, Harrad and Hopf.